Indo-US Strategic Convergence: Implications for South Asia - Sabiha Mehreen; Iraj Abid (CISS Insight Journal, 2022)
The United States (US) dominance in the current global order has been challenged by China’s economic rise in the twenty-first century. The US has always sought allies and strategic partners in different regions to counter any threats it faces globally. In South Asia, the US has partnered with India to counter the rising influence of China in Asia-Pacific (APAC) region and to maintain its dominant status in the world. This strategic convergence has two-fold implications: (i) Fuelling the great-power rivalry; and (ii) Creating strategic instability in the region, as it is one of the theatres of conflicts between the great powers. This, in turn, diminishes the prospects of peace in South Asia and increases the risk of conflict escalation between the two nuclear-armed rivals in South Asia – Pakistan and India. The paper examines the evolution and nature of Indo-US strategic convergence in the twenty-first century and its impact on strategic stability in South Asia.